2017
DOI: 10.5551/jat.36467
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Contributes to the Development of Non-Calcified Coronary Plaque: A 5-Year Computed Tomography Follow-up Study

Abstract: Aim: Epicardial adipose tissue (EAT) has been suggested as a contributing factor for coronary atherosclerosis based on the previous cross-sectional studies and pathophysiologic background. However, a causal relationship between EAT and the development of non-calcified coronary plaque (NCP) has not been investigated.Methods: A total of 122 asymptomatic individuals (age, 56.0 ± 7.6 years; male, 80.3%) without prior history of coronary artery disease (CAD) or metabolic syndrome and without NCP or obstructive CAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
2
24
1
2
Order By: Relevance
“…25 Similar follow up studies states that EFT on CT is independently predicting the development of non-calcium coronary plague in asymptomatic patients especially in type II diabetes. 17,26 In contrast to previous study Meenakshi K et al showed no significant difference in EFT among male and female patients with matched BMI in both gender and gender is not affecting the correlation between EFT and CAD. 18 Ng et al used 3D echocardiography in 130 patients and found that EFT affects the systolic function of left ventricle despite of preserved ejection fraction and absence of significant CAD.…”
Section: Coronary Artery Diseasecontrasting
confidence: 57%
“…25 Similar follow up studies states that EFT on CT is independently predicting the development of non-calcium coronary plague in asymptomatic patients especially in type II diabetes. 17,26 In contrast to previous study Meenakshi K et al showed no significant difference in EFT among male and female patients with matched BMI in both gender and gender is not affecting the correlation between EFT and CAD. 18 Ng et al used 3D echocardiography in 130 patients and found that EFT affects the systolic function of left ventricle despite of preserved ejection fraction and absence of significant CAD.…”
Section: Coronary Artery Diseasecontrasting
confidence: 57%
“…All of these studies supported the paracrine effect of EAT by creating local inflammation, from outside to inside the coronary artery, and contributed to atheromatous plaque formation. [47][48][49][50] Without studying the inflammatory marker of EAT, we could only ask the question but could not confirm this hypothesis in this reported case.…”
Section: Eat a New Risk Predictormentioning
confidence: 71%
“…They found that epicardial fat is independently and linearly associated with CAD severity. Recently, Hwang et al, 49 performed a serial Coronary Computerized Tomogram of coronary artery (CTA) in 122 asymptomatic cases who had no CAD at baseline study. After the mean follow up of 65.4 months, EAT and diabetes mellitus independently predicted the development of new non-calcified plaque with the odd ratio of 4.29 and 9.0 respectively.…”
Section: Eat a New Risk Predictormentioning
confidence: 99%
“…Previous studies have reported an association among epicardial fat volume (EFV), obstructive coronary artery disease [2], coronary artery calcium score (CACS) [3,4], and high-risk plaque measured on cardiac CT [5]. This relationship is thought to be a result of production of inflammatory mediators by EF and its CVIA proximity to the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%